(untitled) (Filološke studije, 2019)
The understanding, retention and recollection of learning materials depends on complex interactions between the cognitive and motivational characteristics of the recipient, in particular his/her knowledge, learning strategies and standpoints on the one hand, and, on the other, the way information is presented in the learning material, e.g. type of content, organisation and sequence. Integrative processing depends on formal characteristics of the text or picture, which more or less speed up the processes of connecting information from both sources. This involves the question of the structural complementarity of the learning material. Some organisational parts of the text, for example headings, abstracts and picture captions, may direct the reader’s attention to the pictures. We talk about structural complementarity when, for example, a picture or a sentence is used to direct the reader’s attention to a scheme that allows him/her to understand the content of the other medium. One of the main conditions of integrative processing is therefore an explicit direction from one medium to the other, usually from the text as the principal medium to the illustration.